ANALYZING STUDENTS’ CONSTRUCTION OF THE RELATIONSHIP BETWEEN CONTINUITY AND DIFFERENTIABILITY - Nasrun, Nasrun; Ikram, Muhammad (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2023)
Abstract: The relationship between continuity and differentiability in graphical problems are two concepts that students are pivotal in understanding derivative concepts. However, researchers rarely pay attention to how students understand the relationship between Continuity and differentiability or vice versa. This study investigates students’ understanding of the relationship between continuity and differentiability. This study is exploratory and focuses on the meanings students construct. The participants were 195 third-year undergraduate students from various Indonesian universities. A questionnaire and interview were used to collect data. Ten of the participants agreed to an in-depth interview for exploration and clarification. Thematic analysis was used to deduce patterns from participants’ responses based on the findings. The results indicated that students construct three types of meanings when they solve problems: physical, analytical, and covariational. The findings could serve as a conceptual framework for future learning processes emphasizing continuity and differentiability. Abstrak: Hubungan antara kontinuitas dan diferensiasi dalam soal grafis merupakan dua konsep yang sangat penting bagi siswa dalam memahami konsep turunan. Namun peneliti jarang memperhatikan bagaimana siswa memahami hubungan antara Kontinuitas dan diferensiasi atau sebaliknya. Penelitian ini menyelidiki pengetahuan siswa tentang hubungan antara kontinuitas dan diferensiasi. Penelitian ini bersifat eksploratif dan berfokus pada makna yang dibangun siswa. Pesertanya adalah mahasiswa S1 tahun ketiga dari berbagai universitas di Indonesia yang berjumlah 195 orang. Kuesioner dan wawancara digunakan untuk mengumpulkan data. Sepuluh peserta menyetujui wawancara mendalam untuk eksplorasi dan klarifikasi. Analisis tematik digunakan untuk menyimpulkan pola tanggapan peserta berdasarkan temuan. Hasilnya menunjukkan bahwa siswa membangun tiga jenis makna ketika mereka memecahkan masalah: fisik, analitis, dan dan kovarian. Temuan ini dapat berfungsi sebagai kerangka konseptual untuk proses pembelajaran di masa depan yang menekankan kontinuitas dan diferensiasi.